Surface Nanostructuring of a CuAlBe Shape Memory Alloy Produces a 10.3 ± 0.6 GPa Nanohardness Martensite Microstructure - Figueroa, Carlos Gabriel (Materials (Basel), 2020)
Severe plastic deformation (SPD) has led to the discovery of ever stronger materials, either by bulk modification or by surface deformation under sliding contact. These processes increase the strength of an alloy through the transformation of the deformation substructure into submicrometric grains or twins. Here, surface SPD was induced by plastic deformation under frictional contact with a spherical tool in a hot rolled CuAlBe-shape memory alloy. This created a microstructure consisting of a few course martensite variants and ultrafine intersecting bands of secondary martensite and/or austenite, increasing the nanohardness of hot-rolled material from 2.6 to 10.3 GPa. In as-cast material the increase was from 2.4 to 5 GPa. The friction coefficient and surface damage were significantly higher in the hot rolled condition. Metallographic evidence showed that hot rolling was not followed by recrystallisation. This means that a remaining dislocation substructure can lock the martensite and impedes back-transformation to austenite. In the as-cast material, a very fine but softer austenite microstructure was found. The observed difference in properties provides an opportunity to fine-tune the process either for optimal wear resistance or for maximum surface hardness. The modified hot-rolled material possesses the highest hardness obtained to date in nanostructured non-ferrous alloys.